On the applicability of the assessment of dental tooth wear for the study of collective prehistoric burials - Marado, Luís Miguel (2018)
Teeth are a very important resource in Biological Anthropology. One of their many uses is the evaluation of dental wear, which can document both masticatory and non-masticatory behavior. The objectives of this work are to 1) present a protocol for scoring evidence of non-masticatory activity applicable to all kinds of contexts (including commingled collective burials), 2) suggest interpretation tools, and 3) use simple, time-saving and accessible procedures. Procedures addressing oral alterations, a new trait – cingular continuous lesions (CCL) – and statistical analysis are described. This method will complement archaeological knowledge on past populations’ cultural, ritual or work-related tooth uses.